2007
DOI: 10.1111/j.1600-065x.2006.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of mathematical immunology

Abstract: The types of mathematical models used in immunology and their scope have changed drastically in the past 10 years. Classical models were based on ordinary differential equations (ODEs), difference equations, and cellular automata. These models focused on the 'simple' dynamics obtained between a small number of reagent types (e.g. one type of receptor and one type of antigen or two T-cell populations). With the advent of high-throughput methods, genomic data, and unlimited computing power, immunological modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 138 publications
(165 reference statements)
0
44
0
Order By: Relevance
“…Detailed information about various types of models of immune system dynamics published in the immunological and mathematical literature is beyond the scope of this review, but can be found in several excellent reviews (e.g. Morel, 1998;Nowak and May, 2000;Yates et al, 2001;Perelson, 2002;Louzoun, 2007;Kirschner and Linderman, 2009). …”
Section: Prrsv (Virus) Infection (See Example 1)mentioning
confidence: 99%
See 4 more Smart Citations
“…Detailed information about various types of models of immune system dynamics published in the immunological and mathematical literature is beyond the scope of this review, but can be found in several excellent reviews (e.g. Morel, 1998;Nowak and May, 2000;Yates et al, 2001;Perelson, 2002;Louzoun, 2007;Kirschner and Linderman, 2009). …”
Section: Prrsv (Virus) Infection (See Example 1)mentioning
confidence: 99%
“…Traditional conceptual approaches are replaced by more data-driven approaches and mathematical systems with few components giving way to large networks. Citing Louzoun (2007), 'mathematical modelling in immunology is becoming more and more molecular'.…”
Section: Doeschl-wilsonmentioning
confidence: 99%
See 3 more Smart Citations